Future of Parathyroid hormone and its analogues in dentistry (International Journal of Scientific Research and Management (IJSRM), 2014)
Bone remodeling is a highly coordinated physiological process orchestrated by cross talks between various cells, pathways and signaling molecules that are required to repair damaged bone and maintain mineral homeostasis. Bone regeneration is a complex physiological process that aims to restore the original function and architecture of bone lost in cases of trauma, fracture, abnormal bone healing etc. To achieve this goal of bone regeneration, various bone substitutes like bone grafts, osteogenic stem cells, osteoconductive scaffolds, growth factors, barrier membranes have been used with mixed results.